Using a Narrative Approach to Understanding the Frontline Practices and Experiences of Aboriginal and Non-Aboriginal Child Protection Workers - Pooyak, Sherri; Gomez, Yvonne (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2009)
This article reflects on the use of narrative analysis in understanding the experiences of two women, one Aboriginal and the other non-Aboriginal, each practicing in child welfare environments opposite of their cultural identities and worldviews.